Problems of Organizing Internal Evaluation in Schools in the Educational Context of Uzbekistan (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
For the economic growth of the country, students need not only proper education in school, but also monitoring and evaluation in education. From this point of view, in this article, whether there is a need to improve the system of internal monitoring in schools or not, gaps in the organization of school monitoring were studied. In the study, a questionnaire was conducted with the participation of 106 respondents, consisting of school principals and candidates. The results of the survey were analyzed using the mathematical-statistical analysis method. Uzbekistan education in the context of it was determined that there is a need to improve the system of internal monitoring of the quality of education in schools, there is a need for independent evaluation and monitoring organizations that conduct internal monitoring in schools and create a road map for their individual development.